Mind the gap: The extent of violence against women with disabilities in Australia: The - Dowse, L.; Soldatic, Karen; Spangaro, J.; Van Toorn, G. (Australian Social Policy Association, 2016)
© Australian Social Policy Association. A comprehensive national response to violence against women with disabilities is long overdue in Australia. Work to date suggests that the issue is endemic yet largely invisible. Responses at the national level are hampered by the lack of information regarding violence against women with disabilities due to under-reporting and inadequate capture of the prevalence of this violence. This article explores approaches to collecting data regarding violence against women with disabilities in Australia and adds to the limited body of knowledge about the prevalence of violence for these women through interrogation of available data. Further analysis of the 2012 Personal Safety Survey data indicates that among women with disabilities aged under 50, 62 per cent have experienced violence since the age of 15, and women with disabilities had experienced three times the rate of sexual violence in the past 12 months compared to those without disabilities. These findings still do not represent the full extent of violence against women with disabilities, since the Personal Safety Survey samples only women who reside in private dwellings and excludes those living in disability care settings. Insight is offered as to what is needed to comprehensively capture the required data and the implications for policy.